2014
DOI: 10.1093/humrep/deu121
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone replacement with vaginal gel versus i.m. injection: cycle and pregnancy outcomes in IVF patients receiving vitrified blastocysts

Abstract: STUDY QUESTIONDoes the type of luteal support affect pregnancy outcomes in recipients of vitrified blastocysts?SUMMARY ANSWERLuteal support with vaginal progesterone gel or i.m. progesterone (IMP) results in comparable implantation and pregnancy rates in IVF patients receiving vitrified blastocysts.WHAT IS KNOWN ALREADYIn fresh IVF cycles, both IMP and vaginal progesterone have become the standard of care for luteal phase support. Due to conflicting data in replacement cycles, IMP is often considered to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 30 publications
(48 reference statements)
4
52
0
3
Order By: Relevance
“…Currently, there are three different routes of administration of exogenous P4; vaginal, intramuscular, and oral [5,6]. When compared to human chorionic gonadotropin (HCG), the use of P4 luteal support is preferable to the use of HCG because it performs better in FET cycles [7] and has a lower chance of ovarian hyperstimulation syndrome [5].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are three different routes of administration of exogenous P4; vaginal, intramuscular, and oral [5,6]. When compared to human chorionic gonadotropin (HCG), the use of P4 luteal support is preferable to the use of HCG because it performs better in FET cycles [7] and has a lower chance of ovarian hyperstimulation syndrome [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is substantial evidence that intramuscular and vaginal routes have comparable ongoing pregnancy/live birth rates [67] in fresh autologous cycles, there is controversy in FER cycles. In FER cycles, some studies reported better pregnancy outcome with intramuscular route [68,69], whereas the majority of the studies reported similar pregnancy outcome [70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, several clinical groups view vaginal administration of progesterone as superior to other routes (Ho et al, 2008;Manno et al, 2005;Tavaniotou et al, 2000). Conversely, a recent investigation has demonstrated that vaginal gel and intramuscular injection of progesterone showed comparable implantation and pregnancy rates in IVF patients receiving vitrified blastocysts (Shapiro et al, 2014). Therefore, we are not aware of any utero-vaginal portal venous system that might enable a true first pass effect for progesterone, nor do we believe that vaginal pessaries saturate the pelvic tissues to any significant degree for direct absorption.…”
Section: Figurementioning
confidence: 99%